2019
DOI: 10.1177/1040638719852374
|View full text |Cite
|
Sign up to set email alerts
|

Molecular methods in detection and epidemiologic studies of rabbit and hare viruses: a review

Abstract: Various PCR-based assays for rabbit viruses have gradually replaced traditional virologic assays, such as virus isolation, because they offer high-throughput analysis, better test sensitivity and specificity, and allow vaccine and wild-type virus strains to be fully typed and differentiated. In addition, PCR is irreplaceable in the detection of uncultivable or fastidious rabbit pathogens or those occurring in low quantity in a tested sample. We provide herein an overview of the current state of the art in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…PCR also facilitates virus gene sequencing so that all vaccine and wild-type virus strains can be fully typed and differentiated. PCR can also be used for the detection of pathogens that are difficult to be isolated using traditional methods and those that are present in low titer in test samples [ 24 ]. The virus VP60 gene has been selected as a target [ 25 ] for reverse-transcription PCR (RT-PCR) assay which is currently used as a general screening tool for rabbit and hare caliciviruses.…”
Section: Introductionmentioning
confidence: 99%
“…PCR also facilitates virus gene sequencing so that all vaccine and wild-type virus strains can be fully typed and differentiated. PCR can also be used for the detection of pathogens that are difficult to be isolated using traditional methods and those that are present in low titer in test samples [ 24 ]. The virus VP60 gene has been selected as a target [ 25 ] for reverse-transcription PCR (RT-PCR) assay which is currently used as a general screening tool for rabbit and hare caliciviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The real-time PCR method is a technique that successfully replaces classic PCR in virological research. Due to its high efficiency and the possibility of quantifying a small number of viral particles, it is widely used in research on L. europaeus, including its diagnostics [25]. The list of primers used in published analyses using the real-time PCR method is presented in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several in-house protocols have been developed for the use of real-time RT-PCR, from genotype-specific to multiplex detection and quantification of lagoviruses, each adapted to the needs and epidemiological background of the region, e.g., [7,27,31,134,154,155]. A comprehensive review on such methods has been recently reported by Kwit and Rzeżutka (2019) [138]. Commercial kits are also available from, for example, Ingenetix and Genesig.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…In addition, it was successfully used for RHDV detection from formalin-fixed, paraffin-embedded archived tissues further allowing retrospective studies [ 135 ]. However, nRT-PCR is more time-consuming and requires more a priori information on the target sequence than conventional RT-PCR [ 138 ].…”
Section: Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation